Faktor-Faktor yang Mempengaruhi Kualitas Kinerja Kantor Pertanahan Rote Ndao - Geraldino A. Sayd; Frans Gana; Petrus Kase (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
The aim of this research is to analysis the inﬂuence of determinant (input) and process factors toward the performance (output) quality of Land Agency in Rote Ndao Regency. Variables used in this study are six independent variables and one dependent variable. The six independent variables are human resources supply, budget supply, facilities supply, infrastructure supply, bureaucracy eﬃciency and work dicipline, whereas the dependent variable is performance quality. The population of this study consists of 30 employees Land Agency in Rote Ndao Regency. Sampling techniques is sampling saturated. Data analysis used in this research is Spearman’s correlation analysis. Data analysis result shows that the six independet variables have signiﬁcant inﬂunce toward the dependent variable partially and simultaneously.